Optimasi Fungsi Keanggotaan Fuzzy Mamdani menggunakan Algoritme Genetika untuk Penentuan Kesesuaian Lahan Tanam Tembakau - Fikri Hilman; Budi Darma Setiawan; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the requirements for good quality tobacco is a good land use. Improved quality of the land will result in increased quality and quantity of tobacco plants produced. The main constraints experienced by tobacco farmers in determining land suitability are the limited knowledge and difficulty of obtaining correct data on the quality of land suitable for tobacco plants. Therefore, a computerized system is needed to assist farmers in making decisions on prospective land to be used. This system is implemented using Fuzzy Inference System (FIS) Mamdani and optimized using Genetic Algorithm. Some of the factors used in this system include the percentage of land affected by the disease, the openness of the region, the degree of weight of the soil, the thickness of the layer, the ease of irrigation, terrain conditions, and soil pH. The reproduction method used is extended intermediate crossover and random mutation, while the selection method used is elitism. Based on the results of the tests that have been done, the most optimum solution obtained on the total number for 90 population , the combination of cr and mr value of 0.2 and 0.8 respectively and the number of generations of 500, with the average of fitness value generated of 0,917. The Accuracy generated by this system is 80 % using 10 test data.